Combined trabeculotomy-trabeculectomy compared with primary trabeculectomy for congenital glaucoma. - Elder, M J (1994)
This paper aimed to assess the outcome of primary trabeculectomy for congenital glaucoma and to compare it with a combined trabeculotomy-trabeculectomy procedure. The combined procedure was assessed using a prospective trial for children with primary glaucoma under the age of 1 year (n = 16). The primary trabeculectomy was assessed retrospectively using similar patients treated at the same hospital from 1981 to 1990 (n = 44). After 24 months of follow up, the cumulative chance of success of the primary trabeculectomy was 72% and this was compared with the combined procedure of 93.5%. Primary trabeculectomy achieved good intraocular pressure control for up to 10 years. Follow up for the combined procedure ranged from 19 to 27 months. Complications included hyphaema (4/16 and 4/44) and cataract (0/16 and 3/44). Primary trabeculectomy for congenital glaucoma gives adequate long term success with few complications. The combined procedure may have a higher success rate and this requires further investigation.